(untitled) (Journal of Current and Advance Medical Research, 2021)
Background: There are several risk factors and diseases related with the acute kidney injury among neonates. Objective: The purpose of the present study was to find out the risk factors and primary disease responsible for acute kidney injury among neonates. Methodology: This cross-sectional study was conducted in the Department of Paediatric Nephrology at Bangabandhu Sheikh Mujib University, Dhaka, Bangladesh from May 2018 to July 2019 for a period of one year. Patients with the age group of less than 1 months who were at risk of AKI, and admitted in the inpatient department of Pediatrics and allied at Bangabandhu Sheikh Mujib University, Dhaka, Bangladesh in both sexes were selected as study population. To detect AKI, serum creatinine was measured at 0 h (baseline), 48 h and 5th day respectively. Result: A total number of 52 patients who fulfilled the inclusion criteria were enrolled in this study. Among them 10 cases were in neonatal age group. The mean age was 10.8±5.4 days with female predominance. The risk factors of AKI in neonate was only pre-renal; mostly due to hypovolemia which was 3(60.0%) cases followed by sepsis and asphyxia which were 1(20.0%) case in each. The most patients had sepsis which was 4(40.0%) cases followed by congenital heart disease which was 2(20.0%) cases; one presented with heart failure and another one had cyanotic congenital heart disease. Conclusion: In conclusion hypovolemia, sepsis and asphyxia are the most common risk factors of acute kidney injury among the neonates. Journal of Current and Advance Medical Research, January 2021;8(1):12-16